Comparing hail risk management strategies through whole-farm multi-period stochastic budgeting for avocado production in South Africa - Steyn, Theunis Christian (Stellenbosch : Stellenbosch University, 2020)
Thesis (MCom)--Stellenbosch University, 2020.